2013
DOI: 10.1002/cne.23309
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ghrelin receptor gene in neurons of the medulla oblongata of the rat

Abstract: There is ambiguity concerning the distribution of neurons that express the ghrelin receptor (GHSR) in the medulla oblongata. In the current study we used a sensitive nonradioactive method to investigate GHSR mRNA distribution by in situ hybridization. Strong expression of the GHSR gene was confirmed in neurons of the facial nucleus (FacN, 7), the dorsal vagal complex (DVC), and the semicompact (but not compact) nucleus ambiguus (AmbSC and AmbC). In addition, expression of GHSR was found in other regions, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 75 publications
(131 reference statements)
0
22
0
Order By: Relevance
“…Although the highest concentration of it is found in the pituitary gland and hypothalamus, consistent with the known role of ghrelin in GH release and the regulation of body weight and metabolism [10,11], there is also abundant GHSR-1a expression in other, extra-hypothalamic areas including the cortex and brain stem [12-17] suggesting that ghrelin plays a much broader role [10,18,19]. A recent comparative study on hippocampal and cortical dissociated neurons showed that GHSR-1 mRNA expression is higher in the hippocampus than in the cortex, and depends on the maturation stage of the cultures [20].…”
Section: Introductionmentioning
confidence: 75%
“…Although the highest concentration of it is found in the pituitary gland and hypothalamus, consistent with the known role of ghrelin in GH release and the regulation of body weight and metabolism [10,11], there is also abundant GHSR-1a expression in other, extra-hypothalamic areas including the cortex and brain stem [12-17] suggesting that ghrelin plays a much broader role [10,18,19]. A recent comparative study on hippocampal and cortical dissociated neurons showed that GHSR-1 mRNA expression is higher in the hippocampus than in the cortex, and depends on the maturation stage of the cultures [20].…”
Section: Introductionmentioning
confidence: 75%
“…However, in the NTS known to receive afferent terminals of the gastric vagal innervation, we found only a small‐number of Fos‐ir cells in 6‐OHDA rats treated with HM01 compared to almost none by vehicle. In contrast, there was a 12.7‐fold increase in the number of Fos positive cells in the AP where GHS‐R1a are strongly expressed . This points to HM01 possible action through brainstem circuits regulating gastric function via the AP.…”
Section: Discussionmentioning
confidence: 91%
“…The protocols for probe design and in situ hybridization have been described previously (Bron et al, ). In brief, the Fam38B (Piezo2), TRPM8, c‐Ret, and TrkB genes were identified in the guinea pig genome sequence (Broad Institute; Boston, MA; see http://asia.ensembl.org/Cavia_porcellus/Info/Index).…”
Section: Methodsmentioning
confidence: 99%